SISTEM INFORMASI RENTAL MOBIL BERBASIS WEB MENGGUNAKAN WHATSAPP GATEWAY PADA RENTAL MOBIL SASHA - Sri Wana; Adi Candra; Juniarti Iryani (journal Informatika, Multimedia, dan Informasi, 2024)
This research aims to: (1) Design a Web-based car rental information system using Whatsapp gateway at Sasha Car Rental. (2) Implement a web-based car rental information system using Whatsapp gateway at Sasha Car Rental. (3) Knowing the response of Sasha car rental owners and tenants to the car rental website that has been designed. This research uses the Waterfall method, which is a development model that describes a systematic and sequential approach to software development. The stages used in the Waterfall model include: (1) Requirement Analysis (2) System Design (3) Implementation (4) Integration & Testing (5) Operating & Maintenance. Based on the results of the discussion of the Web-based car rental information system using Whatsapp Gateway at Sasha Car Rental, it can be concluded (1) This website-based system uses the Waterfall method, which in its design uses the PHP programming language with the Codeigniter 3 Framework, MySQL Database Management System, Sublime software as a text editor, and Chrome / Mozilla FireFox as a browser. And using Whatsapp Gateway as a sender of notification messages to customers. In this system there are 2 users, namely admins and customers who want to rent a car at Sasha Car Rental. (2) Web-based car rental information system using Whatsapp Gateway at Sasha Car Rental which has been created to be used to facilitate customers in terms of car rental and facilitate owners in managing their car rental. Based on the results of its implementation, it is obtained that this system is running well where the output is in accordance with what is desired by users and rental owners. (3)The response of car rental owners to the Sasha Car Rental Website, namely giving a "positive" response which can be seen in the total average percentage of 84.93%. From these results, it can be interpreted that the Sasha Car Rental Website has a good response and high attractiveness, and with the Sasha Car Rental Website can help and facilitate rental owners and their customers.